Timbulan, Komposisi dan Karakteristik Sampah Bahan Berbahaya dan Beracun (B3) pada Sarana Kesehatan - Yenni Ruslinda; Ragil Nur Permadi (Jurnal Dampak, 2018)
Hazardous Solid Waste (HSW) are typically found on the packaging of the products with explosive, flammable, and toxic features, which are the characteristics of HSW. This waste is not only generated from industrial activities but also generated from household, commercial, and institutional activities. This study aims to analyze the generation, composition and characteristics of HSW from health facilities such as hospitals and health centers, with case studies in Padang City. Measurements of generation are carried out in weight and volume units, composition measurements by type of use, and characteristics measurement based on literature and regulations. Method of measurement was in accordance with SNI 19-3964-1994, with 11 samples and carried out for eight days in a row. The result of measurement shows that HSW generation at health facility was 0.02354 kg/person/day in weight unit or equal to 0.18600 l/person/day in volume unit. The HSW were come from the packaging of body care medication and other medical wastes with the characteristics classified as toxic, corrosive and infectious